2020
DOI: 10.21203/rs.3.rs-23596/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Platelet count as a biomarker for monitoring treatment response and disease recurrence in recurrent epithelial ovarian cancer

Abstract: ObjectivesWe sought to determine the impact of pretreatment plasma platelet levels, dimerized plasmin fragment (D-dimer) and fibrinogen in recurrent epithelial ovarian cancer (EOC) and the impact of platelet levels on SKOV3 cell lines growth and responsiveness to chemotherapy. MethodsUnder approval of ethical committee, we identified 104 women with recurrent EOC who underwent treatment between January 2010 and February 2015. Reviewing clinical, laboratory, and pathologic records from this retrospective cohort,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…That study found that the greater the PLR value was associated with better progression-free survival (Badora-Rybicka et al, 2016). A change in this ratio could be caused by various things, including changes in platelet and lymphocyte levels after surgery (Hu et al, 2020). In contrast, Raungkaewmanee et al found that the PLR value over 200 was associated with more aggressive tumors and lower patient survival (Raungkaewmanee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…That study found that the greater the PLR value was associated with better progression-free survival (Badora-Rybicka et al, 2016). A change in this ratio could be caused by various things, including changes in platelet and lymphocyte levels after surgery (Hu et al, 2020). In contrast, Raungkaewmanee et al found that the PLR value over 200 was associated with more aggressive tumors and lower patient survival (Raungkaewmanee et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Tumors can cause abnormalities in platelet counts and functions of activation and aggregation. Platelet counts have been shown to be a prognostic predictor for patients with a variety of tumors, including lung, ovarian, prostate, colon cancers, and melanoma [2][3][4][5]. Abnormal activation and aggregation of platelets, especially tumor-activated platelets, may lead to thrombosis, especially cancerrelated thrombosis, which may cause death in cancer patients [6,7].…”
Section: Introductionmentioning
confidence: 99%